CURRENT COMMENT. (America Magazine: The Jesuit Review of Faith & Culture, 1968)
This section offers comments on political and social topics and issues around the world. The fight for a U.S. Federal open housing law shifts to the House of Representatives. It mentions the preparation of an Education Act for the management of all schools in Kenya. Also noted is the boundary problems confronting Guyana.